Interpretive discrepancies caused by target values inter-batch variations in chemiluminescence immunoassay for SARS-CoV-2 IgM/IgG by MAGLUMI - Selingerova, Iveta; Valik, Dalibor; Gescheidtova, Lenka; Sramek, Vladimir; Cermakova, Zdenka; Zdrazilova-Dubska, Lenka (Journal of medical virology, 2021)
Plasma specimens from coronavirus disease 2019 patients were double-tested for anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies by two different batches of MAGLUMI 2019-nCov immunoglobulin M/immunoglobulin G (IgM/IgG) assays to evaluate IgM/IgG levels, qualitative interpretation, antibody kinetics, and linearity of diluted specimen. Here we show that (i) high-level IgM specimens need to be diluted with negative human plasma but not kit diluents and (ii) measured anti-SARS-CoV-2 IgM/IgG concentrations are substantially higher with later marketed immunoassay batch leading to (iii) the change of qualitative interpretation (positive vs. negative) in 12.3% of specimens measured for IgM, (iv) the informative time-course pattern of antibody production only when data from different immunoassay batches are not combined.
Keywords: imunoanalýza; Immunoglobulin M; luminiscence; COVID-19 Testing; Sensitivity and Specificity; Immunoglobulin G; Luminescence; Humans; senzitivita a specificita; Immunoassay; testování na COVID-19; Antibodies, Viral; Luminescent Measurements; CLIA; lidé; SARS-CoV-2; anti-SARS-CoV-2 IgG; anti-SARS-CoV-2 IgM; luminiscenční měření; inter-assay batch variation; interpretative inconsistency; imunoglobulin G; protilátky virové; imunoglobulin M; COVID-19